Superior nano-mechanical properties of reduced graphene oxide reinforced polyurethane composites1. Issue 22 (11th March 2015) - Gupta, Tejendra K.; Singh, Bhanu P.; Tripathi, Ravi Kant; Dhakate, Sanjay R.; Singh, Vidya N.; Panwar, O. S.; Mathur, Rakesh B.
<x xml:space="preserve">Abstract</x> RGO reinforced polymer composites with significantly enhanced nanomechanical properties useful for automobile, wind mill blade industries and also in hard and scratch-less coatings on automotive vehicles have been synthesized.